Distribution Management System and Control Architecture through a FPGA device for Electrical Distribution Feeders - Ibarra Hernandez, Frank Alberto (2016)
This paper proposes the utilization of VHDL (Very High Speed Integrated Circuit plus Hardware Description Language) for developing a novel Distribution Management System (DMS) and control architecture for electrical distribution systems. Developed DMS and control architecture utilizes a FPGA (Field Programmable Gate Array) device allowing electrical feeder control. This DMS and control architecture in its case study gives priority to control a voltage regulator, based on the switching TAP change (for each phase). The test case system used in this research consists of a 959 nodes distribution feeder, considering a typical real Brazilian electrical-distribution radial system. Some results for the distribution feeder test case are presented, in order to demonstrate the feasibility of the developed higher-level control using a FPGA device in a VHDL platform.